Bioinspired Functional Catechol Derivatives through Simple Thiol Conjugate Addition. Issue 53 (3rd September 2019) - Mancebo‐Aracil, Juan; Casagualda, Carolina; Moreno‐Villaécija, Miguel Ángel; Nador, Fabiana; García‐Pardo, Javier; Franconetti‐García, Antonio; Busqué, Félix; Alibés, Ramon; Esplandiu, María José; Ruiz‐Molina, Daniel; Sedó‐Vegara, Josep
Abstract: The combination of the surface‐adhesive properties of catechol rings and functional moieties conveying specific properties is very appealing to materials chemistry, but the preparation of catechol derivatives often requires elaborate synthetic routes to circumvent the intrinsic reactivity of the catechol ring. In this work, functional catechols are synthesized straightforwardly by using the bioinspired reaction of several functional thiols with o ‐benzoquinone. With one exception, the conjugated addition of the thiol takes place regioselectively at the 3‐position of the quinone, and is rationalized by DFT calculations. Overall, this synthetic methodology provides a general and straightforward access to functional and chain‐extended catechol derivatives, which are later tested with regard to their hydro‐/oleophobicity, colloidal stability, fluorescence, and metal‐coordinating capabilities in proof‐of‐concept applications. Abstract : Functional catechols : A systematic methodology for the synthesis of functional catechol derivatives has been reported. This procedure affords a wide variety of moieties, which can be used as coatings for the modification of the wettability of macroscopic surfaces, the stabilization of colloidal dispersions, and the preparation of fluorescent markers for theranostic nanoparticles in biomedical applications.